ANALYSIS ABOUT THE IMPACT OF ‘KABUPATEN APBD’ BUDGET ALLOCATION AGAINST THE POVERTY IN INDONESIA 2006-2009 - Dimas Ari Darmantyo (The Management Journal of Binaniaga, 2016)
This research aims to analyze the impact of APBD/counties/ regency/city budget allocation against the poverty in Indonesia for the period of 2006 – 2009. By using the panel data of 172 regencies/cities, this research has found that the allocation of APBD budgeting is not pro-poor oriented, but it could have the possibility to reduce the poverty level. The result of this research has explained that low rate of the inflation could reduce the poverty level itself.Keywords:  budgeting allocation, APBD (counties, district, city  budgeting), pro-poor, poverty level.